Makna Simbol di Balik Puisi “Rumahku” Karya Chairil Anwar - Rahma Sari; Dwi Wahyu Candra Dewi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Chairil Anwar's poem "My Home" reflects the inner struggle and search for identity in a life full of uncertainty. This study uses a qualitative descriptive method to explore the meaning of the symbols contained in the poem. Symbols such as "home," "tent," "twilight," and "clear glass" are depictions of feelings of alienation, confusion of direction, and a desire for peace that is not physical, but spiritual. The results of the study show that this poem is not only an aesthetic expression, but also a medium for understanding the dynamics of the human mind in facing reality. Chairil Anwar positions poetry as a space for self-protection and a place to search for the meaning of life. The implications of this study strengthen the understanding that literature, especially poetry, has an important function as a means of reflection and existential expression in facing the complexities of life.